2013
DOI: 10.1080/09602011.2013.811087
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and depression in left and right hemisphere post-stroke patients

Abstract: Background and Purpose Although it is well accepted that depression and stress are closely related in the general adult population, this link is less understood in post-stroke patients. Due to the high occurrence of depression in post-stroke patients it is important to look closely at this possible association. The current study explores perceived stress and depression in post-stroke patients. Methods Nineteen left hemisphere (LH) stroke patients and 12 right hemisphere (RH) post-stroke patients were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
1
30
0
3
Order By: Relevance
“…This finding supports and expands the previous results of Laures-Gore and Defife 12 indicating that the perception of stress is an important variable in the development of depression in not just stroke patients, but also patients with aphasia. This finding also aligns with recent work in the general area of post-stroke anxiety (PSA) and PSD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding supports and expands the previous results of Laures-Gore and Defife 12 indicating that the perception of stress is an important variable in the development of depression in not just stroke patients, but also patients with aphasia. This finding also aligns with recent work in the general area of post-stroke anxiety (PSA) and PSD.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Laures-Gore and DeFife 12 found that the perception of stress as measured by the Perceived Stress Scale 13 predicted depressive symptoms as measured by SADQ-10 in stroke patients. Indeed, perceived stress was a better predictor of depressive symptoms than severity of neurological impairment.…”
mentioning
confidence: 99%
“…Our findings are consistent with the results of crosssectional study that aimed to identify predictors of perceived stress of 97 stroke survivors immediately after discharge, which showed that more depressive symptoms were related to higher levels of perceived stress (11) . Similarly, a study conducted in the state of Georgia, in the United States, also found a strong positive correlation between perceived stress and depressive symptoms in stroke survivors, regardless of the cerebral hemisphere affected by the stroke (20) . Due to the study design, we cannot infer that stress causes depressive symptoms or depressive symptoms cause stress, however, we can only suggest that these two variables have a strong positive correlation.…”
Section: Resultsmentioning
confidence: 98%
“…At present, we understand little about the association between age, stress, and depression after onset of a chronic illness such as stroke (Hammen, 2005; Laures-Gore & Defife, 2013). As Ouimet et al (2001) suggest, the influence of subjective stress on individuals’ developmental experiences with stroke may be one critical missing piece of the puzzle of explaining the exceedingly high prevalence of depression in the stroke population.…”
Section: Introductionmentioning
confidence: 99%